2009
DOI: 10.1111/j.1439-0434.2008.01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Fungicide Effectiveness during the Various Developmental Stages of Peronophythora litchii In Vitro

Abstract: Litchi downy blight caused by Peronophythora litchii is one of the most destructive diseases suffered by litchi in China. This study has evaluated the activities of the fungicides dimethomorph (DMM), azoxystrobin (AZB), famoxadone (FMD), metalaxyl (MTL), cymoxanil (CYX) and mancozeb (MCB) on the mycelial growth, sporulation, zoospores release, and germination of sporangia as well as of cystospores of P. litchii. Dimethomorph and MTL inhibited mycelial growth more effectively than the other fungicides tested. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…Litchi downy blight is important postharvest disease caused by P. litchii , which leads to considerable losses during storage and transportation 17 18 . The disease is managed principally by application of synthetic fungicides such as mancozeb, cymoxanil, sulfur dioxide and benomyl 7 17 . To deal with the unavoidable emergence of fungicide tolerance and resistance problems, it is critical to discover and identify new antifungal molecules with different mechanisms for the control of this disease 6 7 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Litchi downy blight is important postharvest disease caused by P. litchii , which leads to considerable losses during storage and transportation 17 18 . The disease is managed principally by application of synthetic fungicides such as mancozeb, cymoxanil, sulfur dioxide and benomyl 7 17 . To deal with the unavoidable emergence of fungicide tolerance and resistance problems, it is critical to discover and identify new antifungal molecules with different mechanisms for the control of this disease 6 7 19 .…”
Section: Discussionmentioning
confidence: 99%
“…The disease is managed principally by application of synthetic fungicides such as mancozeb, cymoxanil, sulfur dioxide and benomyl 7 17 . To deal with the unavoidable emergence of fungicide tolerance and resistance problems, it is critical to discover and identify new antifungal molecules with different mechanisms for the control of this disease 6 7 19 . In this study, we showed for the first time that ZMS, a new type of antibiotics produced by Dickeya zeae EC1, can effectively suppress the decay of post-harvest litchi fruits and peel browning caused by P. litchii .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peronophythora litchii is homothallic (self-fertile), and undergoes many short disease cycles per season with a high dispersal of spores over time and space and a random sexual recombination in the disease cycle (1). It could be classified as a medium-high risk pathogen (24).…”
Section: Discussionmentioning
confidence: 99%
“…Control of the disease is based on an integration of several cultural methods with the use of fungicides. In the 1990s, multisite inhibitors, such as mancozeb and chlorothalonil, and the target site-specific phenylamide metalaxyl were used to control this disease (24). A novel fungicide group, the carboxyl acid amide (CAA) fungicides, was first registered in 1996 in China for the control of litchi downy blight (25).…”
mentioning
confidence: 99%